Importancia de la aplicación de técnicas de litigación oral dentro de la audiencia de juzgamiento en un proceso penal en el Ecuador. - Aguilar Gutiérrez, Franshesca Pavlova (2022)
In this appied research proyect, it has been made an análisis of the importance of the application of oral litigation techniques in a criminal proceeding in Ecuador. Was carried out an applid research with a qualitative method, with a correlational and explanatory scope. The research is structured by tour chapters. Regarding the first chapter is about formulation of the problem, general and specifict objetives, and its justification. The second chapter elaborates the theoritical framework. The background of the research, and a theoretical foundation is made in which the oral accusatory system, the orality, the principles of the oral accusatory system, criminal guaratees, oral litigation and the techniques. In addition to the trial hearing, the opening statement, theory of the case, practice of evidence, interrogation, cross-examination, objections, closing arguments, and how to be a good trial lawyer. And the variables of the investigation. As for the third chapter is made a description of the research work. In wich the field of study, the type of research, the level of reseach, the research method, the research desing, the population and sample. In addition to the procedures for data collection and data processing techniques. Finally, in the tourth chapter, the results of investigation are collected. Thus, the results obtained are presented. The beneficiaries, the impacto of the reseach and the transfer of results.